2016
DOI: 10.1364/oe.24.007879
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing high-power Yb-doped fiber amplifier systems in the presence of transverse mode instabilities

Abstract: The average output power of Yb-doped fiber amplifier systems is currently limited by the onset of transverse mode instabilities. Besides, it has been recently shown that the transverse mode instability threshold can be significantly reduced by the presence of photodarkening in the fiber. Therefore, reducing the photodarkening level of the core material composition is the most straightforward way to increase the output average power of fiber amplifier systems but, unfortunately, this is not always easy or possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…However, all of them will produce the increasing of the heat load, and this will result in decreasing of the MI threshold. According to the previous report, the amplifier with counter‐propagating pump configurations has a higher MI threshold comparing to the co‐propagating pump configurations. Moreover, it has a higher SRS threshold.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, all of them will produce the increasing of the heat load, and this will result in decreasing of the MI threshold. According to the previous report, the amplifier with counter‐propagating pump configurations has a higher MI threshold comparing to the co‐propagating pump configurations. Moreover, it has a higher SRS threshold.…”
Section: Resultsmentioning
confidence: 82%
“…It includes to reduce pump absorption level by modifying the fiber design. Until now, the influence of various fiber laser parameters on MI, such as pump wavelength, pump directions, signal wavelength, core/cladding radio have been studied theoretically and experimentally. However, from our knowledge, no strategy or experiment about reducing the pump absorption level by broadening the pump linewidth has ever been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that TMI sets in well before the conventional TL limit is reached, following closely a (1/d0) 2 dependence in very good agreement with our theory. It should be noted that use of the alternative TMI power threshold [7], which in this case takes the simplified form PTMI2 = 34(ηlaser/ηheat)L, would have resulted in a TMI threshold of ~105W, independent of core diameter. …”
Section: Thermal Lensing and Tmi Comparisonmentioning
confidence: 98%
“…In these studies, different TMI power threshold formulae were considered giving different power limits. In [5] the TMI threshold is considered to be reached at a fixed average heat load of Q0=34W/m, independent of core diameter [7], and predicts a diode-pumped power limit of 70kW, defined though by SRS and TL. In [6] the TMI threshold scales inversely with core area and the diode-pumped power limit is ~28kW.…”
Section: Introductionmentioning
confidence: 99%
“…In general, minimizing PD by core material composition is advised as the solution for increasing the output power of high-power fiber lasers limited by TMI. When not possible, active ion concentration and the core conformation should be optimized to reduce TMI [8].…”
Section: Introductionmentioning
confidence: 99%